2024
DOI: 10.1002/hed.27675
|View full text |Cite
|
Sign up to set email alerts
|

Vascular events in patients with head and neck cancer: A systematic review and meta‐analysis

Neil P. Monaghan,
Kelsey A. Duckett,
Shaun A. Nguyen
et al.

Abstract: ObjectiveTo assess the incidence of vascular events in patients with head and neck cancer.Review MethodsPrimary studies identified through April 2023. Meta‐analysis was performed.ResultsThere were 146 studies included in the systematic review. Rates of events were collected in the overall group, those with chemoprophylaxis, and those that underwent surgery, radiation, or chemotherapy. Of 1 184 160 patients, 4.3% had a vascular event. Radiation therapy had highest risk of overall events and stroke when compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 168 publications
(216 reference statements)
0
0
0
Order By: Relevance
“…However, a literature search reveals a review article published by Haen et al [5], concluding that HNCs have biological/molecular characteristics associated with a high risk of VTE/AT, albeit with a low incidence rate. In fact, Monaghan et al [6] reported a vascular event incidence of 4-5%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a literature search reveals a review article published by Haen et al [5], concluding that HNCs have biological/molecular characteristics associated with a high risk of VTE/AT, albeit with a low incidence rate. In fact, Monaghan et al [6] reported a vascular event incidence of 4-5%.…”
Section: Discussionmentioning
confidence: 99%
“…The meta-analysis by Monaghan et al [6] describes that patients receiving radiotherapy have a higher frequency of vascular events compared to surgery and chemotherapy. Indeed, a recent study [7] concerning surgical procedures reported an incidence rate of 1.3%.…”
Section: Discussionmentioning
confidence: 99%